Estado e sociedade civil na cooperação internacional: perspectivas dos países doadores, receptores e do Brasil - Leonardi, Ramon Santoro (Universidade Federal de São Carlos, 2010)
This essay is on the relationship between State and civil society, through the angle of international cooperation. The work has two parts. The first studies the concept of civil society, on its multiple meanings through modern period and its possible contemporary instances as political project. The second inquires the international cooperation relationships between donor and receptor countries, considering different actor perspectives. The analysis focus on years between 2002-2008, and a part of the explanation details Brazil case. Moreover, this study aims to contribute on the globalization debate, mainly on its effects over power framework and world order.
Keywords: Relações internacionais; Teoria política; Globalização; Geopolítica; Política externa; Política internacional; Cooperação internacional; Ajuda internacional; Sociedade civil; International relations; International cooperation; Foreign aid; Civil society; CIENCIAS HUMANAS::CIENCIA POLITICA